Ikatan Orangtua-anak Dalam Perilaku Seksual Berisiko Remaja - Frivana, Eby; Ramadani, Mery; Yenti, Melisa (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: There has been an increase in risky sexual behavior among adolescents in Indonesia. As many as 12% of women report having experienced an unwanted pregnancy. Parental bonding has been identified as a crucial factor.Objective: To determine the relationship between parental bonding and risky sexual behavior in adolescents.Method: Cross-sectional design with a sample of 231 students. Data were analyzed using multiple logistic regression. Odds ratios were calculated by controlling for covariates suspected of interfering with the relationship between parental bonding and risky sexual behavior.Results and Discussion: 52.4% of adolescents engaged in high-risk sexual behavior, while 47.6% felt less bonded with their parents. More than half experienced high peer influence (56.3%), were quite religious (52.4%), lived with a complete family (81.8%), and had a moderate socioeconomic status (50.2%). Adolescents with less parental bonding were 43 times more likely to engage in risky sexual behavior after controlling for peer role, social media, religiosity, and family structure.Conclusion: More than half of adolescents engaged in high-risk sexual behavior and had less parental bonding. There is a significant relationship between parental bonding and risky sexual behavior.